Cultural Capital dan Kharisma Kiai dalam Wacana Partai Politik - Muazaroh, Siti; Subaidi, Subaidi (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2019)
Kiyai has quite significant influence among the community despite aligning double roles as caregivers of boarding schools as well as politicians. This article examines the Maimun Zubair nanny Pondok pesantren A-Anwar Sarang and also chairman of the Sharia Assembly Party Development Association (PPP) using the analysis of the mutualist symbiotic theory of Al-Ghozali by mirroring the cultural capital theory of Bourdieu. The results of this research can be suggested that the first figure Maimun Zubair Kiyai can position his role on the structure and as an agent. Second, Maimun has a charisma in the community despite the politics of the world. With the charism still preserved and the determination of the relation in religious affairs and state should beplaced in its position and in good cooperation and balanced, so as to minimize the conflict in political parties.